동일 데이터를 이용한 구조방정식 툴 간의 비교분석 - 남수태; 김도관; 진찬용; Nam, Soo-tai; Kim, Do-goan; Jin, Chan-yong (한국정보통신학회논문지, 2018)
Structural equation modeling is pointing to statistical procedures that simultaneously perform path analysis and confirmatory factor analysis. Today, this statistical procedure is an essential tool for researchers in the social sciences. There are as AMOS, LISREL and PLS representative tools that can perform structural equation modeling analysis. AMOS provides a convenient graphical user interface for beginners to use. PLS has the advantage of not having a constraint on normal distribution as well as a graphical user interface. Therefore, we compared and analyzed the three most commonly used tools (applications) in social sciences. Based on structural equation modeling, confirmatory factor analysis was performed using the IBM AMOS Ver. 23, the LISREL 8.70 and the SmartPLS 2.0. The comparative results show that LISREL has the highest explanatory power of dependent variables than other analytical tools. The path coefficients and T-values presented by the analysis results showed similar results for all three analysis tools. This study suggests practical and theoretical implications based on the results. 구조방정식 모델링은 경로분석 및 확인적 요인분석을 동시에 수행해 주는 통계적 절차를 따르고 있다. 오늘날이 통계적 절차는 사회과학 분야의 연구자에게 필수적인 도구이다. 구조방정식 모델링 분석을 해주는 대표적인 도구로는 AMOS, LISREL 그리고 PLS가 있다. AMOS는 초보자가 사용할 수 있도록 편리한 그래픽 사용자 인터페이스를 제공해 주고 있다. PLS는 그래픽 사용자 인터페이스뿐만 아니라 정규분포에 대한 제약조건도 없다는 장점을 가지고 있다. 또한 사회과학 분야에서 가장 많이 사용하는 3가지 도구 (applications)를 비교분석 하였다. 구조방정식 모델링 기반 확인적 요인 분석은 IBM AMOS Ver 23, LISREL 8.70 및 SmartPLS 2.0을 사용하였다. 구조방정식 모델링 비교 분석 결과는 LISREL이 다른 분석 도구보다 종속 변수의 설명력이 가장 높음을 확인할 수 있었다. 분석 결과에 의해 제시된 경로계수 값 및 T 값은 3가지 분석 도구 모두 유사한 결과를 보이는 것으로 나타났다. 따라서 이러한 결과를 바탕으로 이론적 실무적 시사점을 제시하였다.